Evaluating the effectiveness of the rural minimum living standard guarantee (Dibao) program in China - Kakwani, Nanak; Li, Shi; Wang, Xiaobing; Zhu, Mengbing (China economic review, 2019)
China's Rural Minimum Living Standard Guarantee program (Dibao) is the largest social safety-net program in the world. Given the scale and the popularity of Rural Dibao, it is necessary to rigorously evaluate it so that policymakers know the extent to which the program meets its intended objective of reducing poverty. This paper develops some new methods and uses data from the 2013 Chinese Household Income Project (CHIP2013) to examine the targeting performance of the rural Dibao program. The paper has found that the Rural Dibao program suffers from very low targeting accuracy, high exclusion error, and inclusion error, and yields a significant negative social rate of return. It discusses possible causes and argues that the fundamental mechanism has to be redesigned to increase the effectiveness of the program. The paper makes some recommendations to reform Dibao that will significantly improve targeting and reduce the cost of running the program. That will help China to achieve its goal of eradicating extreme poverty by 2020. •The selection of an individual in the rural Dibao program not determined by the poverty status of the individual measured by income or consumption.•Rural Dibao program excluded almost 87% of the poor while included about 82% of the non-poor in 2013.•The poor beneficiaries get much less than those non-poor beneficiaries.•The percentage of total resources leaked out to the non-poor is even higher than the leakage of beneficiaries.•Rural Dibao program yielded high negative social rate of return for both the poverty gap ratio and the severity of poverty.